Answer:
4600
Step-by-step explanation:
This is an arithmetic sequence with common difference d between consecutive terms.
d = - 2 - (- 6) = 2 - (- 2) = 6 - 2 = 4
The sum to n terms of an arithmetic sequence is
=
[ 2a + (n - 1)d ]
where a is the first term
here a = - 6, d= 4 and n = 50, hence
=
[ (2 × - 6) + (49 × 4) ]
= 25 ( - 12 + 196 )
= 25 × 184
= 4600
The answer is B
Hope this helps :)
Answer:
0.614
Step-by-step explanation:
90 is the answer to that question
Answer:
2 + (3 + 4) = (2 + 3) + 4 ⇒2+7 = 5+4.
Step-by-step explanation: